Review on the synthesis of thiourea-triazine hybrid derivatives and its applications primarily in biological context - Ainaa Nadiah, Abd Halim; Zainab, Ngaini (Taylor and Francis, 2025)
Thiourea and triazine are heteroatom scaolds that have been intensively employed for structural modication, particularly in the development of new drugs and the exploration of new applications. Recent advances have initiated the concept of merging these two moieties, maximizing the potential and enhancing the properties. This review is a comprehensive compilation highlighting the various synthesis pathways of the compound comprised of both thiourea and triazine scaolds expressed in the form of fused triazinethione as well as mono-, bis-, and tristhiourea-triazine structures. The produced compounds indenitely showed the potential to be applied to various elds and industries. While this compilation majorly highlighted the biological capabilities of the thiourea–triazine compounds, a glimpse of other material chemistry applications was also included on the basis of the respective compound as documented by precedent literature. Therefore, this review is signicant for structural modication in the eld of synthetic chemistry for intended applications.